2019
DOI: 10.1007/s12471-019-1234-5
|View full text |Cite
|
Sign up to set email alerts
|

Sex differences in coronary artery plaque composition detected by coronary computed tomography: quantitative and qualitative analysis

Abstract: Background Sex differences in the calculation of coronary heart disease risk have been analysed extensively. However, data on coronary plaque morphology diverge. We analysed plaque characteristics in patients with suspected coronary artery disease (CAD) and defined prognostic factors using coronary computed tomography angiography (CCTA). Methods A total of 6,050 consecutive patients underwent CCTA and were enrolled in the registry. Patients with known CAD were excluded.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
25
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 39 publications
(27 citation statements)
references
References 27 publications
2
25
0
Order By: Relevance
“…The higher total plaque burden in males compared with females in our study, known from cohorts with mild to severe calcium load (CACS >1.0 AU) [ 30 , 31 ], holds true also for patients with CACS 0.…”
Section: Discussionmentioning
confidence: 71%
See 2 more Smart Citations
“…The higher total plaque burden in males compared with females in our study, known from cohorts with mild to severe calcium load (CACS >1.0 AU) [ 30 , 31 ], holds true also for patients with CACS 0.…”
Section: Discussionmentioning
confidence: 71%
“…Previous studies enrolling patients with positive CACS above >1.0 AU reported contradictory results [ 30 , 31 ]. Plank et al [ 30 ] analyzed 1050 patients (1:1 propensity score-matched) and found more calcified plaques in males, while females had more mixed and noncalcified plaques.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…This is especially true for sex-specific differences in the development, manifestation, and prognosis of coronary artery plaques. While the prevalence of obstructive CAD is higher in men compared to women, non-obstructive CAD and ischemia with no obstructive coronary arteries (INOCA) are relatively more common in women [1][2][3]. Compared to obstructive CAD, fewer established preventive, diagnostic and treatment options are available for INOCA [4], complicating treatment of CAD, especially in younger women at low cardiovascular risk.…”
mentioning
confidence: 99%
“…Due to the heterogeneity between studies in terms of imaging modalities (invasive optical coherence tomography (OCT) [17,18] versus invasive intravascular ultrasound (IVUS) [19][20][21] versus noninvasive imaging (i.e. coronary computed tomography angiography; CCTA) [1,[22][23][24]) and investigated lesions (non-obstructive or obstructive [1,18,23,24] versus culprit lesions in myocardial infarction [17,19]) results concerning sex-differences were incoherent. In patients undergoing CCTA, the following findings were consistent between most studies: Men have higher plaque burden in terms of number of plaques and plaque volume, obstructive disease is more common in men, and the relative number of non-calcified plaque is higher in women than in men [1,[22][23][24].…”
mentioning
confidence: 99%